Flower drum song - Li, Chin-Yang 1917-; Rodgers, Richard 1902-1979 (Universal Studios, 2006)
"Eine illegal eingewanderte Chinesin kommt nach operettenhaften Schwierigkeiten in San Franzisco unter die Haube." [filmdienst.de]
Original: USA 1962
special features: a classic evolves: from print to stage to screen - Broadway legends Rodgers and Hammerstein adapt the best-selling novel into a theatrical hit and a Hollywood classic ; faces of the east: casting "Flower drum song" - learn how the film was one of Hollywood's first to cast Asian actors as strong Chinese characters who achieve success and happiness ; the songs of "Flower drum song" - from the unforgettable "I enjoy being a girl" to the east-meets-west classic "Chop suey", experience the wonder of these dazzling musical numbers ; an all-access pass to the sets and costumes of "Flower drum song" ; the legacy of Rodgers and Hammerstein ; feature commentary with actress Nancy Kwan and film historian Nick Redman
Bildformat 2.35:1 (anamorph)
Keywords: Film; DVD-Video